Racial discrimination, racial socialization, and crime over time: a social schematic theory model - Burt, Callie Harbin (Criminology, 2017)
Recent studies evince that interpersonal racial discrimination (IRD) increases the risk of crime among African Americans and familial racial socialization fosters resilience to discrimination's criminogenic effects. Yet, studies have focused on the short‐term effects of IRD and racial socialization largely among adolescents. In this study, we seek to advance knowledge by elucidating how racialized experiences—in interactions and socialization—influence crime for African Americans over time. Elaborating Simons and Burt's (2011) social schematic theory, we trace the effects of childhood IRD and familial racial socialization on adult offending through cognitive and social pathways and their interplay. We test this life‐course SST model using data from the FACHS, a multisite study of Black youth and their families from ages 10 to 25. Consistent with the model, analyses reveal that the criminogenic consequences of childhood IRD are mediated cognitively by a criminogenic knowledge structure and socially through the nature of social relationships in concert with ongoing offending and discrimination experiences. Specifically, by increasing criminogenic cognitive schemas, IRD decreases embeddedness in supportive romantic, educational, and employment relations, which influence social schemas and later crime. Consonant with expectations, the findings also indicate that racial socialization provides enduring resilience by both compensating for and buffering discrimination's criminogenic effects.